Adenosine deaminase deficiency: genotype-phenotype correlations based on expressed activity of 29 mutant alleles. - Arredondo-Vega, F X (1998)
Adenosine deaminase (ADA) deficiency causes lymphopenia and immunodeficiency due to toxic effects of its substrates. Most patients are infants with severe combined immunodeficiency disease (SCID), but others are diagnosed later in childhood (delayed onset) or as adults (late onset); healthy individuals with "partial" ADA deficiency have been identified. More than 50 ADA mutations are known; most patients are heteroallelic, and most alleles are rare. To analyze the relationship of genotype to phenotype, we quantitated the expression of 29 amino acid sequence-altering alleles in the ADA-deleted Escherichia coli strain SO3834. Expressed ADA activity of wild-type and mutant alleles ranged over five orders of magnitude. The 26 disease-associated alleles expressed 0.001%-0.6% of wild-type activity, versus 5%-28% for 3 alleles from "partials." We related these data to the clinical phenotypes and erythrocyte deoxyadenosine nucleotide (dAXP) levels of 52 patients (49 immunodeficient and 3 with partial deficiency) who had 43 genotypes derived from 42 different mutations, including 28 of the expressed alleles. We reduced this complexity to 13 "genotype categories," ranked according to the potential of their constituent alleles to provide ADA activity. Of 31 SCID patients, 28 fell into 3 genotype categories that could express <=0.05% of wild-type ADA activity. Only 2 of 21 patients with delayed, late-onset, or partial phenotypes had one of these "severe" genotypes. Among 37 patients for whom pretreatment metabolic data were available, we found a strong inverse correlation between red-cell dAXP level and total ADA activity expressed by each patient's alleles in SO3834. Our system provides a quantitative framework and ranking system for relating genotype to phenotype.